Short day transcriptomic programming during induction of dormancy in grapevine - Fennell, Anne Y.; Schlauch, Karen A.; Gouthu, Satyanarayana; Deluc, Laurent G.; Khadka, Vedbar; Sreekantan, Lekha; Grimplet, Jerome; Cramer, Grant R.; Mathiason, Katherine L. (Frontiers in Plant Science, 2015)
Bud dormancy in grapevine is an adaptive strategy for the survival of drought, high and low temperatures and freeze dehydration stress that limit the range of cultivar adaptation. Therefore, development of a comprehensive understanding of the biological mechanisms involved in bud dormancy is needed to promote advances in selection and breeding, and to develop improved cultural practices for existing grape cultivars. The seasonally indeterminate grapevine, which continuously develops compound axillary buds during the growing season, provides an excellent system for dissecting dormancy, because the grapevine does not transition through terminal bud development prior to dormancy. This study used gene expression patterns and targeted metabolite analysis of two grapevine genotypes, that are short photoperiod responsive (Vitis riparia) and non-responsive (V. hybrid, Seyval) for dormancy development, to determine differences between bud maturation and dormancy commitment. Grapevine gene expression and metabolites were monitored at seven time points under long (LD, 15 h) and short (SD, 13 h) day treatments. The use of age-matched buds and a small (2h) photoperiod difference minimized developmental differences and allowed us to separate general photoperiod from dormancy specific gene responses. Gene expression profiles indicated three distinct phases (perception, induction and dormancy) in SD-induced dormancy development in V. riparia. Different genes from the NAC DOMAIN CONTAINING PROTEIN 19 and WRKY families of transcription factors were differentially expressed in each phase of dormancy. Metabolite and transcriptome analyses indicated ABA, trehalose, raffinose and resveratrol compounds have a potential role in dormancy commitment. Finally, a comparison between V. riparia compound axillary bud dormancy and dormancy responses in other species emphasized the relationship between dormancy and the expression of genes associated with C3HC4-TYPE RING FINGER, NAC DOMAIN CONTAINING PROTEIN 19 transcription factors.